Math, asked by ADAMSHARIEFF, 1 year ago

prove that: cotA+cosecA-1/cotA-cosecA+1=1+cosA/sinA

Answers

Answered by kunalkumarjha101
4
IF YOU LOVE THIS WAY THEN , PLEASE ADD TO BRAINLIEST ANSWER WHICH WILL MOTIVATE ME TO HELP YOU BETTER.
THANK YOU
☺☺☺
Attachments:

kunalkumarjha101: NICE ,FIRST OF ALL START WILL TRIGO ,IT IS VERY INTERESTING ...DO BEST
kunalkumarjha101: with*
ADAMSHARIEFF: ok ill try and visit ur channel
kunalkumarjha101: THANKS ...
kunalkumarjha101: SO SORRY .....
ADAMSHARIEFF: okay sister thanks by the way
Answered by Panzer786
8
Hii friend,

CotA + CosecA-1/CotA - CosecA +1 = 1+CosA/SinA.

We have,

LHS = CotA+CosecA-1/CotA-CosecA+1

=> (CosecA+CotA)-(Cosec²A-Cot²A)/(CotA-CosecA +1) [ Cosec² theta-Cot²theta = 1)


=> (CosecA+CotA)[1-(CosecA-CotA)/ ( CotA-CosecA+1).

=> (CosecA-CotA) ( CotA-CosecA+1)/(CotA-CosecA+1).

=> (CosecA+CotA)

=> (1/SinA + CosA/SinA)

=> (1+CosA/SinA) = RHS

Hence,

LHS = RHS = 1+CosA/SinA..... PROVED......



HOPE IT WILL HELP YOU... :-)

ADAMSHARIEFF: hi
ADAMSHARIEFF: sister
Similar questions